Doves for the rich, hawks for the poor? Distributional consequences of systematic monetary policy - Nils Gornemann; Keith Küster; Makoto Nakajima (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
We build a New Keynesian business-cycle model with rich household heterogeneity. In the model, systematic monetary stabilization policy affects the distribution of income, income risks, and the demand for funds and supply of assets: the demand, because matching frictions render idiosyncratic labor-market risk endogenous; the supply, because markups, adjustment costs, and the tax system mean that the average profitability of firms is endogenous. Disagreement about systematic monetary stabilization policy is pronounced. The wealth rich or retired tend to favor inflation targeting. The wealth-poor working class, instead, favors unemployment-centric policy. One- and two-agent alternatives can show unanimous disapproval of inflation-centric policy, instead. We highlight how the political support for inflation-centric policy depends on wage setting, the tax system, and the portfolio that households have.
Keywords: E12; E21; E24; E32; E52; J64; 330; Monetary Policy; Unemployment; Search and Matching; Heterogeneous Agents; General Equilibrium; Dual Mandate